Speech acts of bartleby`s and lawyer`s utterances in the short story of bartleby the scrivener a story of wall street by Herman Melville - Istiqomatul Fitri (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2017)
yt 1./ws.c.1